2012
DOI: 10.1111/hsc.12005
|View full text |Cite
|
Sign up to set email alerts
|

The use of Talking Mats to support people with dementia and their carers to make decisions together

Abstract: Policy guidelines insist that people with dementia should be involved in decisions about key life choices and transitions. However, as dementia affects both cognitive and communication difficulties, it becomes increasingly difficult to do this, and innovative and effective ways to support people with dementia and their carers to interact with each other are needed. This project, funded by Joseph Rowntree Foundation, examined if Talking Mats, a low-tech communication framework, could support family carers and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 25 publications
0
104
0
1
Order By: Relevance
“…In particular, delays, pauses and hesitations alongside mitigated and elaborated utterances after assessments, invitations, offers, requests or proposals indicate divergent views, disagreement and rejection, and are treated as such (Davidson;Pomerantz, 1984a, b;Schegloff). Murphy et al (2010) and Murphy and Oliver (2013), found that Talking Mats helped couples affected by dementia. Ferm and Saldert (2013) found that when using Talking Mats people used different co-operation strategies when discussing different topics and goals.…”
Section: Assessment and Agreementmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, delays, pauses and hesitations alongside mitigated and elaborated utterances after assessments, invitations, offers, requests or proposals indicate divergent views, disagreement and rejection, and are treated as such (Davidson;Pomerantz, 1984a, b;Schegloff). Murphy et al (2010) and Murphy and Oliver (2013), found that Talking Mats helped couples affected by dementia. Ferm and Saldert (2013) found that when using Talking Mats people used different co-operation strategies when discussing different topics and goals.…”
Section: Assessment and Agreementmentioning
confidence: 99%
“…Similar discussions about daily living activities could also take place by couples at home, without Talking Mats or a facilitator. Independent of context, both partners in a couple have the right to express their views and feel involved (Murphy and Oliver, 2013;Olaison and Cedersund, 2008;Österholm and Samuelsson, 2013).…”
Section: Clinical Implications and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Talking Mats is a communication framework which can help people with dementia (and other communication difficulties) to express their views and opinions [19,20,21]. The system uses a mat, such as a doormat or carpet tile, to which symbols and pictures can be attached by hook and loop tape.…”
Section: Supporting the Expression Of Opinions And Viewsmentioning
confidence: 99%
“…Talking Mats is a low-technology communication framework to help people with communication difficulties to express their views and opinions more effectively [14,15]. The system uses a mat, such as a doormat or carpet tile, to which symbols and pictures can be attached by hook and loop tape.…”
Section: A Low-technology Communication Frameworkmentioning
confidence: 99%